2017
DOI: 10.1111/ina.12389
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter chemical component concentrations and sources in settings of household solid fuel use

Abstract: Particulate matter (PM) air pollution derives from combustion and non-combustion sources and consists of various chemical species that may differentially impact human health and climate. Previous reviews of PM chemical component concentrations and sources focus on high-income urban settings, which likely differ from the low- and middle-income settings where solid fuel (ie, coal, biomass) is commonly burned for cooking and heating. We aimed to summarize the concentrations of PM chemical components and their con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 88 publications
1
26
1
Order By: Relevance
“…Benzo[a]pyrene, the only one of these compounds classified as a Group 1 carcinogen, was not detected in the sample with exclusive LPG/electric use, but exceeded 40 ng/m 3 in the household samples using all three stoves and only the traditional stoves. Compared to other cooking area benzo[a]pyrene concentrations summarized by Secrest et al in a recent review, these are much lower than the concentrations recorded in other rural Chinese households cooking with biomass (means: 100‐636 ng/m 3 ) but still above the European Commission guideline value of 1 ng/m 3 . In contrast to high PAH concentrations in homes burning biomass, Ruiz et al reported much lower PAH levels in homes using electric, compressed natural gas (CNG), and LPG stoves: Average (±SD) indoor concentrations of benzo(a)pyrene were 1.9 ± 0.5, 2.0 ± 0.9, and 1.5 ± 0.6 ng/m 3 in households with electric, CNG, and LPG stoves, respectively.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Benzo[a]pyrene, the only one of these compounds classified as a Group 1 carcinogen, was not detected in the sample with exclusive LPG/electric use, but exceeded 40 ng/m 3 in the household samples using all three stoves and only the traditional stoves. Compared to other cooking area benzo[a]pyrene concentrations summarized by Secrest et al in a recent review, these are much lower than the concentrations recorded in other rural Chinese households cooking with biomass (means: 100‐636 ng/m 3 ) but still above the European Commission guideline value of 1 ng/m 3 . In contrast to high PAH concentrations in homes burning biomass, Ruiz et al reported much lower PAH levels in homes using electric, compressed natural gas (CNG), and LPG stoves: Average (±SD) indoor concentrations of benzo(a)pyrene were 1.9 ± 0.5, 2.0 ± 0.9, and 1.5 ± 0.6 ng/m 3 in households with electric, CNG, and LPG stoves, respectively.…”
Section: Resultscontrasting
confidence: 62%
“…Recent reviews of indoor air pollution and personal exposures in the context of household solid fuel combustion have recommended further research on the chemical components and sources of indoor and personal exposure PM 2.5 . This research can provide insight on several levels: On a more detailed level, chemical components and sources contributing to particle mass are highly relevant to the health impacts of exposure to those particles.…”
Section: Introductionmentioning
confidence: 99%
“…Residential sector emissions are challenging to quantify reliably because of the wide range of imperfect conditions under which fuels are burned, limited emissions measurements (particularly field measurements of cookstoves being used under realistic conditions), and limited data on activity usage Coffey et al, 2017;Secrest et al, 2017). We probe this uncertainty using sensitivity scenarios with low and high BC:TC ratio of residential sector emissions, using the range of estimates compiled by Lacey and Henze (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Aerosol emissions from inefficient cookstoves are important contributors to indoor and ambient air pollution, increasing premature mortality in adults and children Chafe et al, 2014;Cohen et al, 2017;Lelieveld et al, 2015;Liu et al, 2016;Naeher et al, 2007). However, aerosol emissions from the residential sector are subject to large uncertainties in their magnitude and composition Carter et al, 2016;Coffey et al, 2017;Secrest et al, 2017;Stockwell et al, 2015;Zhang et al, 2009). However, aerosol emissions from the residential sector are subject to large uncertainties in their magnitude and composition Carter et al, 2016;Coffey et al, 2017;Secrest et al, 2017;Stockwell et al, 2015;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation